Estimation of Daily Sodium and Potassium Excretion Using Spot Urine and 24‐Hour Urine Samples in a Black Population (Benin) - Mizéhoun‐Adissoda, Carmelle (J Clin Hypertens (Greenwich), 2015)
The 24‐hour urine collection method is considered the gold standard for the estimation of ingested potassium and sodium. Because of the impracticalities of collecting all urine over a 24‐hour period, spot urine is often used for epidemiological investigations. This study aims to assess the agreement between spot urine and 24‐hour urine measurements to determine sodium and potassium intake. A total of 402 participants aged 25 to 64 years were randomly selected in South Benin. Spot urine was taken during the second urination of the day. Twenty‐four‐hour urine was also collected. Samples (2‐mL) were taken and then stored at ‐20°C. The analysis was carried out using potentiometric dosage. The agreement between spot urine and 24‐hour urine measurements was established using Bland‐Altman plots. A total of 354 results were analyzed. Daily sodium chloride and potassium chloride urinary excretion means were 10.2±4.9 g/24 h and 2.9±1.4 g/24 h, respectively. Estimated daily sodium chloride and potassium chloride means from the spot urine were 10.7±7.0 g/24 h and 3.9±2.1 g/24 h, respectively. Concordance coefficients were 0.61 at d=−0.5 g, (d±2SD=−11 g and 10.1 g) for sodium chloride and 0.61 at d=−1 g, (d±2SD=−3.8 g and 1.8 g) for potassium chloride. Spot urine method is acceptable for estimating 24‐hour urinary sodium and potassium excretion to assess sodium and potassium intake in a black population. However, the confidence interval for the mean difference, which is too large, makes the sodium chloride results inadmissible at a clinical level.